Binimetinib versus dacarbazine in patients with advanced NRAS-mutant melanoma (NEMO): a multicentre, open-label, randomised, phase 3 trial. Issue 4 (April 2017) - Dummer, Reinhard; Schadendorf, Dirk; Ascierto, Paolo A; Arance, Ana; Dutriaux, Caroline; Di Giacomo, Anna Maria; Rutkowski, Piotr; Del Vecchio, Michele; Gutzmer, Ralf; Mandala, Mario; Thomas, Luc; Demidov, Lev; et al.
Summary: Background: There are no established therapies specific for NRAS -mutant melanoma despite the emergence of immunotherapy. We aimed to assess the efficacy and safety of the MEK inhibitor binimetinib versus that of dacarbazine in patients with advanced NRAS -mutant melanoma. Methods: NEMO is an ongoing, randomised, open-label phase 3 study done at 118 hospitals in 26 countries. Patients with advanced, unresectable, American Joint Committee on Cancer stage IIIC or stage IV NRAS -mutant melanoma who were previously untreated or had progressed on or after previous immunotherapy were randomised (2:1) to receive either binimetinib 45 mg orally twice daily or dacarbazine 1000 mg/m 2 intravenously every 3 weeks. Randomisation was stratified by stage, performance status, and previous immunotherapy. The primary endpoint was progression-free survival assessed by blinded central review in the intention-to-treat population. Safety analyses were done in the safety population, consisting of all patients who received at least one study drug dose and one post-baseline safety assessment. This study is registered withClinicalTrials.gov, numberNCT01763164 and with EudraCT, number 2012-003593-51. Findings: Between Aug 19, 2013, and April 28, 2015, 402 patients were enrolled and randomly assigned, 269 to binimetinib and 133 to dacarbazine. Median follow-up was 1·7 months (IQR 1·4–4·1). Median progression-free survival was 2·8 months (95% CI 2·8–3·6) in the binimetinib group and 1·5 months (1·5–1·7) in the dacarbazine group (hazard ratio 0·62 [95% CI 0·47–0·80]; one-sided p<0·001). Grade 3–4 adverse events seen in at least 5% of patients the safety population in either group were increased creatine phosphokinase (52 [19%] of 269 patients in the binimetinib group vs none of 114 in the dacarbazine group), hypertension (20 [7%] vs two [2%]), anaemia (five [2%] vs six [5%]), and neutropenia (two [1%] vs ten [9%]). Serious adverse events (all grades) occurred in 91 (34%) patients in the binimetinib group and 25 (22%) patients in the dacarbazine group. Interpretation: Binimetinib improved progression-free survival compared with dacarbazine and was tolerable. Binimetinib might represent a new treatment option for patients with NRAS -mutant melanoma after failure of immunotherapy. Funding: Array BioPharma and Novartis Pharmaceuticals Corporation.